PELAKSANAAN PERAWATAN TAHANAN DI DALAM PENAHANAN BERDASARKANPERATURAN PEMERINTAH NOMOR 58 TAHUN 1999 TENTANG SYARAT-SYARAT DAN TATA CARA PELAKSANAAN WEWENANG, TUGAS DAN TANGGUNG JAWAB PERAWATAN TAHANAN DI LEMBAGA PEMASYARAKATAN KELAS II A KOTA PEKANBARU - Satrio, Andreas; Effendi, Erdianto; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Treatment of prisoners is one of a series of process development and implementation of the penal system will be done in the crease / Branch detention houses, prisons / Branch prisons carried out by prison officers against detainees or prisoners. Based on this understanding, the authors formulate three formulation of the problem, namely: First, How is the implementation of Government Regulation No. 58 of the prisoners or detainees in Penitentiary Class II A Pekanbaru. Secondly, What are the barriers that occur in the implementation of Government Regulation No. 58 in Penitentiary Class II A Pekanbaru. Third, Are efforts made to overcome barriers to the implementation of Government Regulation No. 58 in Penitentiary Class II A Pekanbaru.This type of research can be classified into types sosilogis juridical research, because this research author directly conduct research on the location or point examined in order to provide a complete and clear picture of the problems to be studied. This research was conducted at the Penitentiary Class II A Pekanbaru, while the sample population is a whole party with regard to the issues examined in this study, the data source used, primary data, secondary data, and the data tertiary, technical data collection in this study by questionnaire, interview and literature study then analyzed qualitatively and process data and generate descriptive data and then infer deductivelyFrom the research there are three main issues which can be summarized as follows: First, the implementation of Government Regulation No. 58 of the prisoners or detainees in Penitentiary Class II A Pekanbaru has not been maximized because there are still many shortcomings of infrastructure. Second, barriers that occur in the implementation of Government Regulation No. 58 in Penitentiary Class II A Pekanbaru disebebkan lack of operational cost factors, lack of personnel or skill factor, Penitentiary Class II A Pekanbaru is over capacity. Third, efforts are being made to overcome the barriers to the implementation of Government Regulation No. 58 in Penitentiary Class II A Pekanbaru first to provide budget funding and operational costs are pretty and well in the implementation of treatment for any prisoners, personnel or officers Penitentiary Class II A Pekanbaru must have the appropriate skills and education to be able to nurture and care for prisoners to achieve the goal of treatment of prisoners, Penitentiary Class II A Pekanbaru to be renovated in order to avoid over-capacity by increasing the number of rooms to accommodate inmates who so much.Keywords: Implementation - maintenance - custody